A educação musical na terceira Idade: uma proposta metodológica de sensibilização e iniciação à linguagem musical - Luz, Marcelo Caires (2005)
This research aims to study about the application of a methodological proposal on Musical Education with elderly people. The main objective consists of the systematization and analysis of the results obtained with the methodology implementation of sensitivity and musical initiation experienced by elderly groups. The technique used consisted of the active observation and photographic records of the process, which permitted the presentation of the description and analysis of the attained results on each working stage. This essay includes, initially, the presentation of the pedagogical concepts of the musical education , considering its specification on the working performance together with the elderly segment. During the project, related questions to the aging process as well as the reflecting thoughts and criteria about the musical educator profile when working with elderly people, have been studied. The results of the analysis pointed out the possibility of the musical language learning process alphabetization with elderly people and reflect about myths and social signals linked to musical education and aging . Besides that, describes analytically the sensitivity stage including the work with the sound phenomenon and the properties of the sound, the rhythm development and the dancing as a powerful instrument of musical appreciation. Finally, the analyses of the results attained in the Initiation stage are found as well as the phases, concepts and processes.